Large-scale ethnomedicinal inventory and therapeutic applications of medicinal and aromatic plants used extensively in folk medicine by the local population in the middle atlas and the plain of Saiss, Morocco - El Yaagoubi, Wissal; El Ghadraoui, Lahsen; Soussi, Meriem; Ezrari, Said; Belmalha, Saadia (Ethnobotany Research and Applications, 2023)
Background: In this work, we carried out a thorough ethnomedicinal investigation of the aromatic and therapeutic plants used in several Middle Atlas and the plain of Saiss provinces (central Morocco). Our goal was to gather data on the variety of plants used, their therapeutic applications, and the portions utilized by local inhabitants. Methods: In eight provinces, including Azrou, Ifrane, Elhajeb, Immouzar, Sefrou, Fez, Meknes, and Mrirt, interviews were done during the 2018-2019 season. Descriptive and multivariate statistics were used to analyze the collected data. To assess the value of medicinal plant resources, we estimated the Family Use Value (FUV), Medicinal Use Value (MUV), and Relative Frequency of Citation (RFC). We next sought consensus among the participants on the reported cures for each category of disorders using the ICF. Results: A total of 154 different kinds of aromatic and medicinal plants from 56 different families were discovered, and local people used them for therapeutic purposes. The most recorded family was Lamiaceae, with 14 species and FUV=0.47. Urtica pilulifera L, was the most frequently utilized species and had the highest RFC equal to 0.425. The most frequently utilized preparation techniques were decoction and brewing, and the most frequently administered portions were the leaves and leafy stems. Additionally, the ICF values per use category ranged from 0.53 to 0.97. Cancer was the category with the highest ICF value (0.97). Conclusions: By advancing knowledge of the medicinal flora and preserving ancestors’ wisdom in Morocco’s Middle Atlas and the plain of Saiss, the current study could be of tremendous service. Keywords: Ethnomedicinal, medicinal plants, Middle Atlas, Plain of Saiss, Morocco, traditional medicine.